Establishing a novel model of malignant airway stenosis in rabbit - Lin, Xiaoxiao; Zhou, Liqin; Zhou, Wanting; Li, Yuping; Jin, Xuru; Ye, Min; Chen, Chengshui (Frontiers in Oncology, 2022)
Background: Malignant central airway stenosis is a life-threatening condition. However, treatment of malignant airway stenosis remains challenging. There is currently a severe lack of an excellent animal model of malignant airway stenosis to facilitate treatment approaches. This is the first study to establish a rabbit model of malignant airway stenosis for bronchoscopic interventional studies. Materials and methods: New Zealand White rabbits were used in this study, randomly divided into group A (18 rabbits) and group B (6 rabbits). VX2 fragment suspension was injected into the submucosal layer of rabbits’ airway by bronchoscopy. Bronchoscopic examinations were performed once a week after VX2 tumor implantation to observe tumor growth and the degree of airway stenosis. Randomly three rabbits were generally dissected after weekly bronchoscopic examination in group A. The rabbits reached to III grade airway stenosis were performed stent implantation in group B. Results: A total of 24 rabbits were successfully implanted with VX2 fragment suspension in the airway without significant adverse events and the success rate of tumor growth was 100%. The degree of airway stenosis reaching to III grade took two to three weeks after implantation VX2 tumor. Median survival time of rabbit models without stent implantation and rabbits with stent implantation respectively was 32.5 days and 32.0 days. Conclusions: The implanting method is safe and effective for the establishment of a rabbit model of malignant airway stenosis. When the tumor grows to 2 to 3 weeks, the rabbit model is available for stent implantation. We recommend the models for more preclinical animal studies on bronchoscopic interventional treatments.